Dampak Krisis Ekonomi Eropa Terhadap Perkembangan Ekspor dan Impor Indonesia - Riska Ayu Pramono; Syapsan '; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine how the impact of the European economic crisis associated with the development of the European Union economy and Indonesia to export and import from Indonesia, whether there is a European economic crisis impacts on the development of Indonesian export commodities and imports and how big the impact of the European economic crisis on the development of trade Indonesia and the European Union.The data used in this study is a secondary data was obtained from the official website of the World Bank, the Central Bureau of Statistics (BPS), the European Statistics (Eurostat) and the Ministry of Commerce and Ministry of Industry of the Republic of Indonesia. Data taken include gross domestic product of Indonesia and the European Union, the rate of inflation in Indonesia and the European Union, Rupiah exchange rate against the Euro and the value of exports and imports of Indonesia and the European Union both oil and non -oil and gas, the period from 1992 to 2011.The method used in this research is a quantitative method to calculate the exchange rate or the terms of trade and the trade is descriptive. The results showed that gross domestic product, inflation rate, exchange rate, and the value of exports and imports showed stunted growth, contagion from the sovereign debt crisis of the European Union have a direct impact on the trade market turmoil in 2009. Followed by a weakening of commodity export and import Indonesia showed that the economic crisis in Europe has a direct impact on export and import trading activities in Indonesia. On the value of the terms of trade of Indonesia and the European Union in 1992-2012, showed an average exchange rate of the European Union and the Indonesian trade by 100 percent, this means that the state of Indonesia and the European Union is still mutually beneficial to undertake export and import trading activities amid economic turmoil global unstable sometimes.Keywords : European Economic Crisis , Export and Import Indonesia